Diabetes Mellitus as the Presenting Feature of Friedreich's Ataxia - Garg, Meenal (J Neurosci Rural Pract, 2017)
Patients with Friedreich's ataxia (FA) are at an increased risk of developing diabetes mellitus and glucose intolerance. Diabetes usually develops many years after the initial presentation. We report an 8-year-old girl who initially presented with diabetic ketoacidosis and was treated as a case of insulin-dependent diabetes mellitus. Around a year later, she developed gait problems and ataxia. Cardiac involvement was detected on echocardiography. Genetic testing confirmed the diagnosis of FA. FA should be a diagnostic consideration in children presenting with diabetes and neurological issues, even with early presentation of the former. Early occurrence of diabetes and rapid progression of ataxia in this patient needs a better understanding of underlying genetic mechanisms.